Patterns of Fulfilling Life Needs of Communities Around Mangrove Areas Cemara Beach, Lembar District, West Lombok - Ziad, Muhammad Thoriq; Ichsan, Andi Chairil; Fahrussiam, Fauzan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aims to analyze the pattern of fulfilling the livelihood needs of communities around the mangrove area of Pantai Cemara, West Lombok, as well as to assess the economic contribution of mangroves to community income and identify supporting and inhibiting factors. The study was conducted from December to February 2026 using a descriptive method with a mixed approach (qualitative and quantitative). Data were collected through observation, interviews, questionnaires, and literature studies from 30 respondents selected by purposive sampling. The results of the study show that the community has diverse patterns of fulfilling their livelihood needs, including ecotourism managers, fishermen, beach vendors, street vendors, and MSME actors with different income characteristics. The total economic turnover reaches IDR 66,200,000 per month, with the largest contribution coming from the trade and tourism services sectors (83.1%), while the direct utilization sector accounts for only 16.9%. Supporting factors include the potential of natural resources and community participation, while obstacles include dependence on weather, limited market access, and pressure from land conversion.